Aproximação de 1ª e 2ª ordens para estudo de equações transientes em tubulação de água: um estudo comparativo - Oliveira, Márcio Bandeira de (2014)
This paper provides a comparison between first and second order approaches equations for the characteristics method as a solution to the transient phenomenon in a pipeline. Eight cases were tested, which resulted in sixteen simulations calculations. Sought to demonstrate the efficiency method of characteristics (MOC) to the nearest 1st. order for small variations of the friction factor in relation to the nearest 2nd order confirming the first to be enough, for the examples studied taking into account the friction term stability as a reference. It was also demonstrated a study simulation the hypothetical instability in terms of high friction.